Virulence and Resistance Characterization of Staphylococci-associated Urinary Tract Infection in Pregnant Women in Lagos, Nigeria - Fowora, Muinah A.; Onyeaghasiri, Faustina U.; Omolopo, Ibilola; Aiyedogbon, Adenike; Edu-Muyideen, Idowu O.; Iwalokun, Bamidele A. (European Scientific Journal, ESJ, 2021)
Background: Urinary Tract Infection (UTI) is the most prevalent bacterial infection in developing countries. UTI is sometimes asymptomatic. The occurrence of UTI in pregnancy can result in complications such as premature or low-birth-weight babies. Escherichia coli is the most common cause of UTI followed by Staphylococci species. However, E.coli associated UTI has been well studied while there is paucity of data on the virulence and resistance of Staphylococci-associated UTIs in women. This study aimed to characterize the virulence and resistance genes in Staphylococci species isolated from the urine of pregnant women. Methods: This was a cross-sectional study involving pregnant women attending ante-natal clinic in Lagos State, Nigeria. Clean catch midstream urine specimens were collected from the women and cultured on appropriate agar. Bacteria were identified using both biochemical and molecular methods and evaluated for resistance to antibiotics. Polymerase chain reaction was used to detect the mecA and blaZ resistance genes and the PVL and TSST virulence genes. Results: Staphylococci species were isolated from 21 (26.25%) of the 80 urine samples of which 7 (29%) were Staphylococcus aureus and 17 (71%) coagulase-negative staphylococcus (CoNS). S. epidermidis and S. saprophyticus were the most commonly isolated CoNS. All the isolates tested were resistant to cotrimoxazole, cloxacillin, erythromycin, ampicillin, amoxicillin-clavulanate, and tetracycline. Both blaZ and the mecA genes were detected in the isolates that were phenotypically susceptible to methicillin and cefoxitin. There was an occurrence of the mecA, blaZ and PVL genes in S. saprophyticus in patients who were co-infected with S. aureus. Conclusion: UTI caused by Staphylococci is common among pregnant women. There is a need to consider staphylococcal associated UTI screening in both symptomatic and asymptomatic cases of UTI in pregnant women.